Lesbia : revue lesbienne d'expression, d'information, d'opinion. (Paris : Lesbia, 1984)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : BP 539, 75529 Paris Cédex 11
Frans
Periodiek
Keywords: lesbische vrouwen